2018
DOI: 10.1080/19419899.2018.1488764
|View full text |Cite
|
Sign up to set email alerts
|

Essentialist beliefs and social distance towards gay men and lesbian women: a latent profile analysis

Abstract: Psychological essentialism is the layperson's belief that social categories are natural and entitative. Studies have shown that essentialist beliefs are strongly connected with different types of prejudice. Previous research into essentialist beliefs predominantly used a variable-centered approach to investigate the relationship between essentialist beliefs and prejudice. Extending this research, we used a person-centered approach to explore the relationship between different essentialist beliefs related to se… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 65 publications
0
2
0
Order By: Relevance
“…less desire and intention to participate in activities with individuals who belong to a certain out-group (Bogardus, 1925). Previous research showed that larger social distance towards gays/lesbians is related to higher levels of essentialist beliefs about the social and psychological differences between genders (Agadullina, Lovakov and Malysheva, 2018), which is further related to an increased tendency to discriminate (Huić, Jelić and Kamenov, 2018), as well as to support boundary-enhancing legislation, policies and social services (Roberts et al, 2017).…”
Section: Attitudes Toward Lgbt Parenthoodmentioning
confidence: 98%
“…less desire and intention to participate in activities with individuals who belong to a certain out-group (Bogardus, 1925). Previous research showed that larger social distance towards gays/lesbians is related to higher levels of essentialist beliefs about the social and psychological differences between genders (Agadullina, Lovakov and Malysheva, 2018), which is further related to an increased tendency to discriminate (Huić, Jelić and Kamenov, 2018), as well as to support boundary-enhancing legislation, policies and social services (Roberts et al, 2017).…”
Section: Attitudes Toward Lgbt Parenthoodmentioning
confidence: 98%
“…While variable-centered analyses, which dominate the field, have been extremely useful in their own right, a person-centered approach can make an additional contribution to social psychological research (Osborne & Sibley, 2017), and has found to be useful in investigating prejudicial attitudes toward minority and stigmatized out-groups (e.g., Agadullina, Lovakov & Malysheva, 2018;Adelman & Verkuyten, 2020;Dangubic et al, 2021;Loch et al, 2013;Meeusen et al, 2018;Sibley & Becker, 2012;Sibley & Liu, 2013). Latent profile analysis is a person-centered approach that seeks to identify unobserved subgroups of individuals who qualitatively differ in the particular ways in which they combine, for example, their motivations to respond without prejudice.…”
Section: Person-centered Approachmentioning
confidence: 99%